Modeling eutrophication vulnerability in coastal Louisiana wetlands impacted by freshwater diversion: a remote sensing approach - Brien, Lynn Ferrara (Kansas State University, 2015)
A major strategy in response to rapid degradation and loss of Louisiana’s coastal wetlands has been the construction of siphon diversion projects. The diversions are designed to reintroduce nutrient enriched freshwater from the Mississippi River into wetland ecosystems to combat saltwater intrusion and stimulate marsh growth. The lack of consensus regarding the effects of river diversions on nutrient enrichment of wetland ecosystems is coupled with major concerns about eutrophication. Locating, assessing, and monitoring eutrophic marsh vegetation represent major challenges to understanding the impacts of freshwater diversions. As a result, this study was undertaken to investigate the feasibility of modeling eutrophication vulnerability of a coastal Louisiana marsh receiving turbid Mississippi River water. The major objective was to integrate remotely sensed data with field measurements of vegetation biophysical characteristics and historical ecosystem survey data to delineate landscape patterns suggestive of vulnerability to eutrophication. The initial step in accomplishing this goal was to model the spatial distribution of freshwater impacts using satellite image-based turbidity frequency data associated with siphon diversion operation. Secondly, satellite and spectroradiometer band combinations and vegetation indices optimal for modeling marsh biophysical characteristics related to nutrient enrichment were identified. Finally, satellite image data were successfully integrated with measures of historical and concurrent marsh biophysical characteristics to model the spatial distribution of eutrophication vulnerability and to elucidate the impacts of freshwater diversions.
Keywords: Remote Sensing; wetlands; eutrophication; Coastal Louisiana; restoration management; Environmental management (0474); Natural Resource Management (0528); Remote Sensing (0799)